Experimental and numerical analysis of in situ pull-out tests on rock bolts in claystones. Issue 12 (15th October 2021) - Giot, Richard; Auvray, Christophe; Raude, Simon; Giraud, Albert
Abstract: In situ pull-out tests were performed in claystones at the Andra Underground Research Laboratory of Meuse/Haute-Marne on fully grouted bolts. The bolts were instrumented with strain gauges along their entire length and axial strains were measured from the head to the far end of the bolts, from bolts installation until the end of the pull-out tests. After bolts setting up, one or several neutral points were identified on most of the bolts. The axial strains increased from the head to the far end of the bolts during the pull-out tests. Tests interpretation required numerical modelling to overcome the shortcomings of analytical models, unable to explain the measured axial strain profiles. Numerical modelling was based on a cohesive zone model. The model qualitatively reproduced measured strain distributions and indicated that the bonding between the bolt and the grout is better in the far end of the bolt than at its head. This result is attributed to a more pronounced fracturing during the development of the induced fractured zone at the wall of the gallery, which is typical of these claystones and caused a debonding of the interface at the head of the bolt.